Addressing the Declining Water Level of the Caspian Sea from a Legal Perspective and a Proposal for a New Agreement - Alimusayev, Emin (Review of European and Comparative Law, 2026)
The Caspian Sea is currently experiencing a rapid decline in water levels, with a 46% reduction in water-covered area between 2001 and 2024. Considering the environmental and socio-economic impacts of the problem, legal responses remain fragmented. This article examines existing legal frameworks to determine why current instruments fail to mitigate the problem of water-level decline. This study employs a doctrinal and comparative legal analysis of the domestic legislations of the five Caspian littoral states, alongside a review of existing international agreements. The analysis reveals that current instruments are insufficient. Domestic legislation of the Caspian littoral states remains uneven and fragmented. Kazakhstan’s Ecological Code serves as a notable model for integrating climate regulation and the response to the decline in water levels in the Caspian Sea into national legislation. While international agreements, such as the Tehran Convention, establish general cooperation principles, they lack binding rules for coordinated river-basin management and climate adaptation. Highlighting a recent surge in regional political will, this paper proposes a new agreement. The proposed agreement introduces binding obligations for reservoir release regimes, minimum environmental flows, and a permanent basin regulatory body. By shifting from ad hoc diplomacy to an integrated legal instrument, the proposal provides a plan for ensuring the socio-economic and environmental security of the Caspian region.